THE ECONOMIC INFLUENCE OF FRANCE IN WEST AND CENTRAL AFRICA - Juraj Ondriaš; Mykola Palinchak; Kateryna Brenzovych (Baltic Journal of Economic Studies)
Despite the decolonisation process, France has retained a considerable degree of influence over its former colonies in Sub-Saharan Africa. However, in recent years, this influence has diminished markedly. The purpose of this article is, therefore, to examine the extent of French economic influence in its former colonies in West and Central Africa. The paper begins by examining the long-term impact of France on the extraction of two key commodities, oil and uranium, on the African continent. This is primarily accomplished through French multinational corporations, which have historical ties to the French government and which exert dominant control over the extraction of the aforementioned mineral resources in the countries under examination. The paper then presents a case study of the Bolloré Group, another French multinational firm that has been active on the continent for an extended period of time across a range of sectors within the economies of the countries under study. In conclusion, the article presents a tabular overview of France's position as a trading partner for fourteen of its former colonies in West and Central Africa. The conclusion is that the decline in France's influence on its former colonies is much slower than one might assume based on recent developments in the political and military spheres (where French influence seems to be declining much faster in the 2020s). The decline is also more noticeable in African countries' exports to France than in their imports from France. The gradual and fluctuating nature of this decline makes it premature to ascertain whether the general decline of French influence, whether economic or political-military, in recent years represents a turning point in the emancipation of France's former colonies, or whether it is merely a transient phenomenon.